Transactional Leadership Style, Job Satisfaction and Organizational Commitment to Employee Performance on Collection Section of Bank X Surabaya - Denis Fidita Karya; Rachma Rizqina Mardhotillah; Laila Alfi Sahrin (Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract The main objective of the organization in general is to fulfill the vision and mission of the organization. To meet the achievements in the organization, the initial step is to first form the human resources that are owned to match the description of the needs of the organization. In the process of shaping the character of each individual in the organization, generally the direction of formation is initiated by the leader, because the leader is the determinant of the organization's performance policies. This study aims to determine the transactional leadership style at Bank X in Surabaya. The effect of this leadership style will have an impact on satisfaction and commitment which in turn will improve employee performance. This research is a quantitative type by distributing questionnaires to employees of Bank X in Surabaya using the Smart Partial Least Square. The results showed that the leadership style of leadership had a significant effect on job satisfaction and organizational commitment, this study also found that job satisfaction and organizational commitment had a significant effect on employee performance at Collection Bank X Surabaya.